Gold mineralization associated with the agassiz metallotect and the johnson shear zone, lynn lake greenstone belt, manitoba - M. A. F. Fedikow; D. A. Baldwin; C. Taylor (Canadian Institute of Mining, Metallurgy and Petroleum, 1986)
The Agassiz Metallotect and the Johnson Shear Zone represent two metallogenetic fea tures located within the northern and outhern belts, respectively. of the Aphebian-aged Lynn Lake greenstone belt in northern Manitoba . Numerous gold occu rrences are associated with these two regional features . The tratabound Agas iz Au-Ag deposit with 2.9 million tonnes of 5.2 g/tonne Au and 11.8 g/tonne Ag. occurs within the Agassiz Metallotect. The stratigraphic sequence characterizing the Agassiz Metallotect comprises interlayered ox ide. silicate and sulphide facies iron formations, biotite-rich and siliceous siltstones. and a high Mg- i-Cr basaltic rock that ha previou ly been identified as tholei itic picrite. These rocks can be traced in outcrop and by their INPUT and gradiometric signature for 65 km. The Johnson Shear Zone is an ill-defined 35 km long zone of strucwral disruption that crosscuts volcanic. sedimentary and intrusive rocks and contains numerous vein-type gold occurrences. Both of these metallotects are characterized by their low level of exploration activity and as a result offer excellent residual exploration potential. Rock, basal till and vegetation geochemical techniques applied in the vicinity of the Agassiz deposit indicate the presence of trace element dispersion halos associated with the mineralization. The halos define an exploration target larger than the mineralized zone. Gold occurrences within the two metallotects are described with emphasis on the Agassiz Au-Ag deposit . A wide range of gold occurrence-types is documented including syngencticstratabound , epigenetic-replacement and epigenetic-quartz vein .